Label-free quantitative proteomics distinguishes general- and site-specific host responses to Pseudomonas aeruginosa infection at the ocular surface - Yeung, J. (Proteomics, 2020)
Mass spectrometry-based proteomics by bottom-up approaches enables the unbiased and sensitive profiling of cellular proteomes and extracellular environments. Recent technological and bioinformatic advances permit identifying of dual biological systems in a single experiment, supporting investigation of infection from the perspective of both a host and pathogen. At the ocular surface, P. aeruginosa are commonly associated with biofilm formation and inflammation of the ocular tissues, causing damage to the eye. The interaction between P. aeruginosa and the immune system at the site of infection describes limitations in clearance of infection and enhanced pathogenesis. Here, we profile the extracellular environment (eye wash) of murine ocular surfaces infected with a clinical isolate of P. aeruginosa and detect neutrophil marker proteins, indicating neutrophil recruitment to the site of infection. We also identify the first potential diagnostic markers of P. aeruginosa-associated keratitis. In addition, we define the deepest murine corneal proteome to date and detect proteins, categories, and networks critical to the host response to infection. Moreover, we provide the first identification of bacteria-specific proteins in response to the host during bacterial biofilm formation of the eye. We validate our findings through in silico comparisons and enzymatic profiling. Overall, our work provides comprehensive profiling of the host-pathogen interface and uncovers differences between general and site-specific host responses to infection.